Elucidation of the Solid Electrolyte Interphase Formation Mechanism in Micro‐Mesoporous Hard‐Carbon Anodes (Adv. Mater. Interfaces 8/2022). Issue 8 (11th March 2022) - Alptekin, Hande; Au, Heather; Olsson, Emilia; Cottom, Jonathon; Jensen, Anders CS; Headen, Thomas F.; Cai, Qiong; Drew, Alan J.; Crespo Ribadeneyra, Maria; Titirici, Maria‐Magdalena
Abstract : Micro‐Mesoporous Hard Carbons as Sodium‐Ion Battery Anodes In article number 2101267, Hande Alptekin, Maria Crespo‐Ribadeneyra, Maria‐Magdalena Titirici, and co‐workers investigate hard carbons with tailored bimodal porosities as sodium‐ion anodes. The nature of the innermost solid electrolyte interphase (SEI) sub‐layer controls the performance. F‐containing salts enable a stable SEI, yet enhanced electrolyte decomposition seems unavoidable in carbonate‐based solvents compared to ether‐based systems.